Experimental performance assessment of efficient photoelectrodes for solar hydrogen production - Akgun, Ibrahim; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
This work examines the photoelectrochemical (PEC) performance of Ni-doped Cu2O photocathodes fabricated on a stainless steel (SS316) substrate via spin coating. The specific characterisation studies conducted using the XRD, FE-SEM, Mott-Schottky, and electrochemical characterisation techniques demonstrate that Ni doping alters the electronic structure of Cu2O, enhancing charge-carrier separation and reducing recombination losses. Regarding photocurrent density, pure Cu2O generates roughly 50 mu A cm-2, whereas electrodes doped with 5-10 % Ni achieve values between 250 and 350 mu A cm-2. The maximum hydrogen production rate recorded was 1665 mu mol g-1 h-1 for 10 % Ni-doped Cu2O, representing an estimated two-fold enhancement relative to pure Cu2O. The assessment of film thickness revealed that the four-layer electrodes exhibited excellent performance, achieving hydrogen generation of 1469 mu mol g-1 h-1. The energy and exergy efficiencies rose from roughly 1.5 % for pure Cu2O to over 2.5 % with the incorporation of 10 % Ni. The findings indicate that a combination of Ni and optimal film thickness markedly enhances the effectiveness of Cu2O photocathodes for PEC hydrogen production.
Keywords: Solar energy; Photoelectrochemical; Hydrogen; Spin coating; Photocatalyst; Efficiency; Renewable energy; Ni-doped Cu2O; CU2O; PHOTOCATHODE; Science & Technology - Other Topics; Energy & Fuels